Illiberal Cultural Christianity?: European Identity Constructions and Anti-Muslim Politics - Hennig, Anja (Religions, 2021)
This paper refers to the ambivalence of secularization in order to explain why Cultural Christianity can show both a liberal and illiberal character. These two faces of Cultural Christianity are mostly due to the identity functions that, not only faith-based religion, but a particularly culturalized version of religion, entails. Proceeding from this, it will be demonstrated here how Cultural Christianity can turn into a concrete illiberal marker of identity or a resource for illiberal collective identity. Our argument focuses on the link between right-wing nationalism and Cultural Christianity from a historical-theoretical perspective, and illustrates the latter with the example of contemporary illiberal and selective European memory constructions including a special emphasis on the exclusivist elements.